Pemikiran KH. Ahmad Dahlan dan H.A.R. Tilaar dalam Pembaruan Pendidikan Islam di Indonesia - M Bahru Wahyuning Aji (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2026)
Education in Indonesia continues to face challenges such as the dichotomy in education, a crisis of character, and the demands of globalization and technological advancements. This study aims to analyze the educational philosophies of KH. Ahmad Dahlan and H.A.R. Tilaar through a comparative study of their philosophical foundations, educational objectives, and educational models, as well as to formulate a synthesis of their ideas for the development of modern Indonesian education. The study employs a qualitative approach using literature review and descriptive-comparative analysis. The results indicate that KH. Ahmad Dahlan emphasizes the integration of religious and secular knowledge to cultivate individuals who are faithful, rational, and socially conscious, whereas H.A.R. Tilaar positions education as a humanizing process grounded in democratic, pluralistic, and humanistic values to foster critical and creative individuals. The novelty of this study lies in the synthesis of the two figures’ thoughts within a single integrative-humanistic educational framework that connects religious, academic, social, and democratic dimensions. This synthesis contributes to the development of Islamic education and national education, particularly in strengthening character education, multicultural education, and learner-centered learning in the digital age.